INFLUENCE OF WORK PLACEMENT AND COMPLEXITY OF TASK TO WORK ACHIEVEMENT COMPANY â€œXâ€ MANADO - Pondaag, Adrian; Worang, Frederik G.; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: There are many factors that affect the work achievement of the employees, including the complexity of the task as a step to carry out the frequency and types of tasks according to their abilities and the placement of an effort to create effective work efficiency of employees in order to produce human resource utilization that is optimal for the company to achieve the company's goals. Goals to be achieved from this research are to determine the effect of Work Placement and complexity of tasks simultaneously on the Work achievement in Company â€œXâ€, to determine the effect of the partial Work Placement of Work achievement in Company â€œXâ€ and to determine the effect of task complexity partially on the Work achievement in Company â€œXâ€. This study used quantitative research method, in order to process the data from the financial Company â€œXâ€. Quantitative research methods are research methods dealing with numbers and anything that is measurable in a systematic way of investigation of phenomena and their relationships. Based on these results, the researcher stated that both variables of employment and complexity of the task influence the effectiveness of work achievement. The recommendation the company should consider about additional training/development for the employee.Â Keywords:work placement, complexity of the task, work achievement.